AÇÃO POPULAR: UM MECANISMO DE CONTINUIDADE DA CIDADANIA (Reflection and Critique Law Magazine, 2025)
Popular Action: A Mechanism for Continuity of CitizenshipAbstract: The present work seeks the study and understanding of Popular Action as a mechanism to aid the exercise of citizenship. Understanding that the exercise of citizenship is not limited to exercising the right to universal suffrage at the time of election, but rather that there are a number of attributions inherent to citizenship, since what is called citizenship is a continuous role in life and that all citizens are capable and have legal capacity and instruments for the supervision of public managers and their actions with the use of the public machine, when these are inherent and in detriment to the public patrimony, to entities to which the government part, to the historical and cultural patrimony, the public morality, environmental damages during its litigation. Moreover, the Federal Constitution of 1988, contemplates the Popular Action as a mechanism for the citizen to exercise the supervision in the acts of public managers since any citizen can be active pole in a Popular Action.Keywords: Popular Action. Mechanism. Citizenship. Supervision.